Biochemical Analysis of Pentraxin 3 and Fibrinogen Levels in Experimental Periodontitis Model - Gonca Cayir Keles; Umut Balli; Burcu Ozkan Cetinkaya; Bulent Ayas; Arzu Findik; Zeynep Pinar Keles; Ferda Pamuk (Mediators of Inflammation, 2012)
Objective. Pentraxin 3 (PTX3), newly discovered inflammation marker, is a member of acute-phase proteins. The hypothesis, synthesis of gingival tissue and serum PTX-3 increases in the experimental periodontitis model (with 10-day and 40-day periods), was tested by detecting gingival tissue and serum PTX-3 levels in rats with experimental periodontitis. Methods. Thirty rats were randomly divided into three groups of ten animals each: ligature-induced experimental periodontitis groups (with 10-day (Group1) and 40-day periods (Group2)) and healthy group (Group3). At the end of experimental period, rats were sacrificed, and radiological and histomorphometric analyses were performed on the mandibles. PTX3 levels were measured in gingival tissue and serum samples using ELISA. Plasma fibrinogen levels were measured according to the nephelometric method. Results. Significant alveolar bone resorption and periodontal inflammation were evident in periodontitis groups. Levels of PTX3 in gingival tissue were statistically higher in Group 1 than those in groups 2 and 3 (P<0.01). No significant difference was found in serum PTX3 levels between experimental periodontitis and control groups (P>0.05). Plasma fibrinogen levels were significantly increased in the experimental periodontitis groups (P<0.001). Conclusion. PTX3 seems to be associated with tissue destruction in earlier periods of inflammatory periodontal disease, contrary to the fibrinogen findings.